STRENGTHENING COMMUNITY PARTICIPATION IN PREVENTION OF CORRUPTION THROUGH THE REGULATION INTEGRATED PARTICIPATIVE CORRECTIONAL INSTITUTIONS - Wencislaus Sirjon Nansi (Program magister Kenotariatan Fakultas Hukum Universitas Lambung Mangkurat, 2021)
The Article Entitled “Strengthening Public Participation in the Prevention of Corruption through the Regulation of Integrative Participative Institutions” is a normative study that wants to analyze the importance of the role of public participation in controlling the policies of prisons in Indonesia in order to minimize corrupt practices in prisons. The results of the authors’ study found that there are obstacles in optimizing the role of public participation in efforts to prevent corruption in prisons, that correctional regulations do not strictly and in detail about community participation. Therefore, the solution offered in this paper is that the government or legislators immediately create regulations that accommodate public participation in controlling correctional policies in Indonesia through participatory correctional regulations. So that this can become a legal basis that provides legal certainty for the public to participate in preventing corruption in prisons.